Video Laryngostroboscopy (Bangladesh Journal of Otorhinolaryngology, 2012)
Stroboscopy has improved our understanding of the vocal cord function and has become an important tool in the diagnosis of voice disorders. It has led to changes in diagnosis in approximately 30% of cases when compared to examination with continuous light and mirror. It is important to understand the normal microscopic anatomy of the vocal folds- the plane of movement of the mucosal wave is the superficial layer (Reinkes space) of lamina propria. Opening and closing of the vocal cords during phonation can be easily seen in mirror examination. The use of high speed motion photography demonstrates additional movements. The equipment required includes stroboscope, camera, recorder, monitor and 90 degree telescope. The following parameters are routinely noted -fundamental frequency, periodicity, amplitude, symmetry, glottic closure, mucosal wave, non vibrating portion, supraglottic activity of larynx. Videostroboscopy helps in differentiating superficial lesions of the epithelium from the deeper lesions involving the muscle. It is useful in diagnosis of early malignancy, vocal nodule, differentiating unilateral paralysis from ankylosis of the cricoarytenoid joint, planning and evaluating phonosurgery. The stroboscopy images can be recorded and stored for future medicolegal purposes in professional voice users and monitoring their treatment. DOI: http://dx.doi.org/10.3329/bjo.v18i2.12010 Bangladesh J Otorhinolaryngol 2012; 18(2): 171-178